Non-existence of Equilibrium for the Two-dimensional Three-firms Location Problem - Shaked, A. (Review of Economic Studies, 1975)
Journal Article Non-existence of Equilibrium for the Two-dimensional Three-firms Location Problem Get access A. Shared A. Shared Nuffield College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 1, January 1975, Pages 51–56, https://doi.org/10.2307/2296818 Published: 01 January 1975